Gravimetric and electrochemical statistical optimizations for improving copper corrosion resistance in hydrochloric acid using thiosemicarbazone-linked 3-acetylpyridine - Muhammad Ammar, Mohamad Alwi; Mohammad Norazmi, Ahmad; Izan Izwan, Misnon; Hariy, Pauzi; Erna, Normaya (Royal Society of Chemistry, 2022)
Thiosemicarbazone-linked 3-acetylpyridine (T3AP), was synthesized and tested on copper strips in hydrochloric acid. Gravimetric measurements and electrochemical impedance spectroscopy were used to investigate the optimized inhibitory behavior of T3AP using the response surface methodology (RSM), with the optimized result obtained using a temperature of 42.90 °C, acid concentration of 2.38 M, inhibitor concentration of 3.80 mM, and time of 18.97 h, with inhibition efficiency up to approximately 93%. Validation of the experimental and predicted RSM showed that no significant difference in the inhibition efficiency with the confidence level value up to 97% was obtained. The isotherm study shows that T3AP obeys the Langmuir isotherm adsorption model, with physisorption and chemisorption adsorption mechanisms. The effectiveness of inhibitor performance of T3AP can be visually observed using scanning electron microscopy and X-ray photoelectron spectroscopy. The characterization revealed that the reactive S and N atoms in the T3AP inhibitor form strong chemical adsorption through N-Cu and Cu-S bonds on the copper surface. Computational analysis was also carried out, and we found that the stable energy gap between the occupied and unoccupied molecular orbitals (4.6891 eV) and high binding energy (540.962 kJ mol−1) adsorption from molecular dynamics were in agreement with the experimental findings.